2017
DOI: 10.5851/kosfa.2017.37.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biodiversity of the Spoilage Microbiota in Chicken Meat Using Next Generation Sequencing and Culture Dependent Approach

Abstract: This study investigated the psychrotrophic bacteria isolated from chicken meat to characterize their microbial composition during refrigerated storage. The bacterial community was identified by the Illumina MiSeq method based on bacterial DNA extracted from spoiled chicken meat. Molecular identification of the isolated psychrotrophic bacteria was carried out using 16S rDNA sequencing and their putrefactive potential was investigated by the growth at low temperature as well as their proteolytic activities in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…; Lee et al . ) with reported lipolytic and proteinolytic activity (Stead ; Alquati et al . ; Marchand et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lee et al . ) with reported lipolytic and proteinolytic activity (Stead ; Alquati et al . ; Marchand et al .…”
Section: Discussionmentioning
confidence: 99%
“…The dominant Pseudomonas species detected in this study were identified as P. weihenstephanensis, P. fragi and P. lundensis. These species have been described as potential meat spoilers as well as raw milk spoilers (Shaw and Latty 1982;Labadie 1999;Ercolini et al 2007;Von Neubeck et al 2016;Lee et al 2017) with reported lipolytic and proteinolytic activity (Stead 1986;Alquati et al 2002;Marchand et al 2009;Stoeckel et al 2016). Additionally, isolates could be affiliated to P. versuta, P. meridiana, P. simiae and P. veronii.…”
Section: Spoilage-associated Microbiota On Map Minced Beefmentioning
confidence: 99%
“…Moreover, Acinetobacter spp. are also associated with chicken meat spoilage (Barnes & Impey, 1968;Lee et al, 2017;Nychas et al, 2008;Russell, Fletcher, & Cox, 1996;Zhang et al, 2012). Thus, it is likely that Acinetobacter spp.…”
Section: Acinetobacter Sppmentioning
confidence: 99%
“…are naturally found in live poultry, poultry environment and/or poultry products (Arnaut-Rollier, De Zutter, & Van Hoof, 1999;Ayres & Walker, 1956;Bergeron et al, 2012;van den Bogaard, London, Driessen, & Stobberingh, 2001;Booth & Arnold, 2003;Ellerbroek, 1997;Glendinning, McLachlan, & Vervelde, 2017;Hatew, Delessa, Zakin, & Gollop, 2011;Leahy, 2015;Lee, Kwon, Heo, Kim, & Kim, 2017;Mayes & Takeballi, 1983;Mead & Adams, 1977;Shabbir et al, 2015;Sundheim, Sletten, & Dainty, 1998;Vadehra, Baker, & Naylor, 1970;Zhang et al, 2012). Moreover, the transmission of E. coli and other non-fermenting GNB such as Acinetobacter spp., and Pseudomonas spp from live birds or their products to people has been tangentially reported in the literature (Leahy, 2015;van den Bogaard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of biological relevance, P. congelans , first isolated in Germany and possibly phytopathogenic, is a Gram‐negative fluorescent bacterium associated with the phyllosphere of grasses . It has also been shown recently to be a prominent species in spoiled chicken meat . Shewanella species are Gram‐negative bacteria that inhabit marine environments and that may play a role in human disease.…”
Section: Introductionmentioning
confidence: 99%